Major shifts in Amazon wildlife populations from recent intensification of floods and drought - Bodmer, R.; Mayor, P.; Antunez, M.; Chota, K.; Fang, T.; Puertas, P.; Pittet, M.; Kirkland, M.; Walkey, M.; Ríos, C.; Pérez Peña, P.; Henderson, P.; et al. (Wiley, 2018)
In the western Amazon Basin, recent intensification of river‐level cycles has increased flooding during the wet seasons and decreased precipitation during the dry season. Greater than normal floods occurred in 2009 and in all years from 2011 to 2015 during high‐water seasons, and a drought occurred during the 2010 low‐water season. During these years, we surveyed populations of terrestrial, arboreal, and aquatic wildlife in a seasonally flooded Amazonian forest in the Loreto region of Peru (99,780 km2) to study the effects of intensification of natural climatic fluctuations on wildlife populations and in turn effects on resource use by local people. Shifts in fish and terrestrial mammal populations occurred during consecutive years of high floods and the drought of 2010. As floods intensified, terrestrial mammal populations decreased by 95%. Fish, waterfowl, and otter (Pteronura brasiliensis) abundances increased during years of intensive floods, whereas river dolphin and caiman populations had stable abundances. Arboreal species, including, macaws, game birds, primates, felids, and other arboreal mammals had stable populations and were not affected directly by high floods. The drought of 2010 had the opposite effect: fish, waterfowl, and dolphin populations decreased, and populations of terrestrial and arboreal species remained stable. Ungulates and large rodents are important sources of food and income for local people, and large declines in these animals has shifted resource use of people living in the flooded forests away from hunting to a greater reliance on fish.